Tingkat Pemanfaatan Ikan Layang (Decapterus Spp) Berdasarkan Hasil Tangkapan Pukat Cincin di Perairan Timur Sulawesi Tenggara - Rita L Bubun; Amir Mahmud (Jurnal Airaha, 2016)
Application of the rules of the Decapterus spp fishing in east coastal Southeast Sulawesi has not been implemented in full. This is not available information about utilization extent Decapterus spp. When these condition do not get attention and management wisely, so can trigger exploitation arrest that exceeds maksimum suistanable yield Decapterus spp. The Research purposes is determines the utilization extent of resources Decapterus spp in east coastal Southeast Sulawesi. The method of this research is survey. Schaefer Model was used to estimate the utilization extent Decapterus spp based on the data time series from year 2007 to 2013. The research results show : the average of utilization extent of Decapterus spp in east coastal of Southeast Sulawesi is 89,04 % and the category of the utilization extent is high fishing level.